Prism-Based Spatial Heterodyne Spectrometer with a Fixed Fringe Localization Plane - Zihao Liu; Da Zhang; Huanyu Yang; Chunling Huo (Applied Sciences)
Spatial heterodyne spectroscopy (SHS) based on prism dispersion is a novel technique designed to overcome the limitations of traditional grating-based SHS, which is affected by grating diffraction. However, there are still some challenges with this technique, one of which is that the fringe localization plane (FLP) moves with changes in wavelength. This paper proposes a prism-based tunable SHS where the FLP is fixed, utilizing prism–bimirror–mirror structures. The theoretical spectral resolving power, based on an example, is higher than 1300 in the spectral range from 10,000 cm−1 to 25,641 cm−1 and is approximately 27,595 at 25,641 cm−1. Furthermore, we propose solutions to simplify the motion control system and address the problem of spectral aliasing.